#TITLE_ALTERNATIVE# - MAYA SUBIANTO (19009095), DWI
Shopping is a form of people’s activity in order to fulfill their needs. But nowadays, shopping doesn’t mean forcing people to go to the store directly, because now we know shopping online. Shopping online is becoming behavior in Indonesia. Even though mortal store still does exist, it becomes the researcher’s concern why some people tend to choose online store and some people choose mortal or offline store. There might be a motivation behind shopping online and offline. The problem is, are there any differences between motivation behind shopping online and offline? Shopping motivation can be influenced by many factors. There is external and internal factor. The external factor that we usually see in daily life is advertisements. Nowadays there is online media that can be an option to promote the products. Online media promotion seems to give more advantages because it can grab attention to more people in a short time. On the other side, offline media promotion still exists. The problem is if the offline media promotions might be replaced by online media promotions. The internal factor that seems to have influence to shopping behavior is shopper impulsivity. Impulsivity is defined by Weun, Jones, and Beatty (1997) as the level or degree to which an individual tends to make unplanned, immediate, and unreflective purchase. This factor can not controled by anyone even the shopper themselves. The problem is whether shopper impulsivity really have influence towards shopping behavior. In conducting this research, the researcher uses questionnaire to gather data. The data then would be analyzed by using factor analysis and regression analysis.